Інституційна природа соціально-економічних аспектів функціонування сільського зеленого туризму - Кальченко, Сергій Володимирович; Кальченко, Сергей Владимирович; Kalchenko, Serhii; Попова, Тетяна Вікторівна; Попова, Татьяна Викторовна; Popova, Tetiana (My University, 2021)
UK: За сучасних умов зростає значущість сфери рекреаційних послуг як фактору сприяння соціально-економічного розвитку на національному та регіональному рівнях. Окремо треба зазначити, що галузева специфіка цих видів діяльності передбачає не тільки використання елементів навколишнього середовища, культурних об’єктів тощо в якості ключових складових процесу співпраці із клієнтом, а й дотримання відповідних правил та норм щодо їхнього застосування. Зазначені обставини позитивно впливають на процеси сталого розвитку територіальних громад, регіонів та країни в цілому. Метою даної статті є дослідження теоретичних та методологічних аспектів економічної діяльності суб’єктів сфери сільського зеленого туризму як елементів інституційного середовища на загальнонаціональному та регіональному рівнях. В ході дослідження було проаналізовано змістовну частину Положеннями загальнонаціональної Стратегії розвитку туризму та курортів на період до 2026 року. Доведено об’єктивність тенденцій інституціоналізації представників туристичної галузі як невід’ємного елементу адаптації національної економічної моделі до стандартів постіндустріального суспільства. Обґрунтовано логічність послідовність «інституція» - «інститут», коли традиції та звичаї людського суспільства з часом знаходять свою функціональну реалізацію у вигляді відповідного соціально-економічного утворення. Обґрунтовано необхідність інституціоналізації суб’єктів господарювання, зайнятих в сфері сільського зеленого туризму як запоруки їхнього подальшого ефективного функціонування. EN: Introduction. Under modern conditions, the importance of recreational services as a factor in promoting socio-economic development at the national and regional levels is growing. Increasing the level of entrepreneurial activity in the fields of tourism and hotel and restaurant business has a positive effect on the level of employment of the local population, improving incomes, restraining depopulation processes and more. It should be noted that the industry specifics of these activities include not only the use of elements of the environment, cultural sites, etc. as key components of the process of cooperation with the client, but also compliance with relevant rules and regulations for their application. These circumstances have a positive impact on the processes of sustainable development of territorial communities, regions and the country as a whole. The purpose of this article is to study the theoretical and methodological aspects of economic activity of rural green tourism entities as elements of the institutional environment at the national and regional levels. Results. During the study, the content of the Regulations of the National Strategy for Tourism and Resorts for the period up to 2026 was analyzed. The objectivity of the tendencies of institutionalization of the representatives of the tourist branch as an integral element of the adaptation of the national economic model to the standards of the post-industrial society is proved. The logic of the sequence "institution" - "institution" is substantiated, when the traditions and customs of human society eventually find their functional realization in the form of a corresponding socio-economic formation. Conclusions. The article highlights the theoretical, methodological and practical aspects of the activities of rural green tourism entities in the system of institutional relations. The study proves the institutional nature of the field of recreational services as those aimed at meeting the basic needs of man as a biological being and a member of society. An analysis of the evolution of tourism and its transformation into a form of entrepreneurial activity as a result of the interaction of socio-economic institutions. Institutional aspects of conducting recreational activities are formulated. The necessity of institutionalization of business entities engaged in the field of rural green tourism as a guarantee of their further effective functioning is substantiated.
Institutional nature of socio-economic aspects of the functioning of rural green tourism
Keywords: сільський зелений туризм; соціальна ефективність; інститут; інституція; сталий розвиток; rural green tourism; social efficiency; institute; institution; sustainable development